Impact of Different Conflict Levels on Culturally Diversified Japanese Organisations’ Performance under a Collaborative Conflict Management Style - Giang Nguyen; Vikas Kumar (International Journal of Organizational Business Excellence, 2021)
With the increasing globalization, cultural diversity management has emerged as an important issue and it is regarded as a process that helps to maintain a positive workplace environment where the similarities and differences of individuals from different cultural backgrounds are valued and shared. The current research examines the impacts of levels of conflict on Japanese organisations’ performance as well as how the collaboration conflict management style influences this relationship. Drawing on conflict management literature and the five levels of conflict from Speed Leas’ Conflict model, the research develops a research model to examine the moderating effect of collaborative conflict management style (CCMS) on the relationship between different levels of conflicts and organisational performance. Data gathered from 58 Japanese and non-Japanese employees in Japanese companies. Data is analysed through SPSS and two-way ANOVA. The results indicate that conflict intensification triggers a negative impact on organisational performance. It also reveals that at different levels of conflicts, collaboration style has various impacts on the performance.